Poverty Condition of Lipa’ Saqbe Mandar Weavers: Initial Findings from Agriculture Area of West Sulawesi, Indonesia - Nurlaela Nurlaela; Nur Adyla S; Akhsan Akhsan; Anwar Sulili; Muhammad Aswad (International Journal of Agriculture System, 2018)
Lipa' Saqbe Mandar (or just called Lipa' saqbe) is an unique culture of Mandar ethnic, it is still preserved today, because the Mandar people wear Lipa' Saqbe at every event held both in traditional ceremonies of Mandar culture like weddings or grief moments. Lipa' Saqbe weavers are the majority of mandarist fishermen and the wives of the peasants who in the concept of indigenous culture mandar adheres to the principle of Siwali Parriq which means the wives of Mandar descendants are able to work to help the family economy, one of them by weaving. This paper attempst to calculate weavers household who are living below poverty line and how severe they are? The study employed Foster- Greer-Torbecke (FGT) Indices Method: Head Count Index (HCI) and Poverty Gap Index (PGI). The results show that: (1) HCI of the study is 0.7333 indicate that 70.33% of Lipa' Saqbe weaver is living below poverty line, while (2) PGI reveals that the depth of poverty in weaver household is, however, close to zero (0) indicating that no poverty severity gap among households. The low income of Mandar silk weavers is the marketing system through traders or distributors. Although most of the weavers sell their woven products directly to the local market, the purchasing power of local communities is quite low so that their woven products are sold to wholesalers or distributors.